(untitled) (Research, Society and Development, 2021)
Although it is true that the interpretation of administrative law is assisted by an undeniable autonomy, it should not be understood as a justification for declaring oneself a foreigner or alien to the legal system that currently governs, that is, the constitutional state of law. The objectives of this research are to systematize the legal interpretation of administrative rules and present their relationship with fundamental rights. The article has used the legal-theoretical method, with deductive technique. In that sense, the interpretation in the administrative headquarters cannot disregard the constitutional principles and rights, otherwise various fundamental rights of the administrated would be violated, highlighting among them, the administrative legal security and the sustainability.